PENINGKATAN BRANDING KEDAI DE VIJAS MELALUI WEBSITE LINKTREE - Hidayah, Muhammad Bilal Nur; Febriana, Poppy; Rochmaniah, Ainur; Ariko, Muhammad Firmansyah Alana Marsa (Fokus ABDIMAS, 2024)
The problem faced by business owners is that the promotion carried out by Kedai De Vijas Kopi has not yet been evenly distributed. The purpose of this Community Service activity is to provide solutions to the existing problems. The method used includes providing guidance on cafe management, offering training to the head barista, and creating a website to enhance the brand image of the cafe. Therefore, MSME operators need to be trained on developing their businesses by promoting Kedai De Vijas through a Linktree website for Instagram, TikTok, and location promotion, so that the marketing system becomes better, expanding the business's target reach and supporting better sales activities.